Leaf cuticle analyses: implications for the existence of cutan/non-ester cutin and its biosynthetic origin. (28th March 2020) - Leide, Jana; Nierop, Klaas G J; Deininger, Ann-Christin; Staiger, Simona; Riederer, Markus; de Leeuw, Jan W
Abstract: Background and Aims: The cuticle of a limited number of plant species contains cutan, a chemically highly resistant biopolymer. As yet, the biosynthesis of cutan is not fully understood. Attempting to further unravel the origin of cutan, we analysed the chemical composition of enzymatically isolated cuticular membranes of Agave americana leaves. Methods: Cuticular waxes were extracted with organic solvents. Subsequently, the dewaxed cuticular membrane was depolymerized by acid-catalysed transesterification yielding cutin monomers and cutan, a non-hydrolysable, cuticular membrane residue. The cutan matrix was analysed by thermal extraction, flash pyrolysis and thermally assisted hydrolysis and methylation to elucidate the monomeric composition and deduce a putative biosynthetic origin. Key Results: According to gas chromatography–mass spectrometry analyses, the cuticular waxes of A. americana contained primarily very-long-chain alkanoic acids and primary alkanols dominated by C32, whereas the cutin biopolyester of A. americana mainly consisted of 9, 10-epoxy ω-hydroxy and 9, 10, ω-trihydroxy C18 alkanoic acids. The main aliphatic cutan monomers were alkanoic acids, primary alkanols, ω-hydroxy alkanoic acids and alkane-α, ω-diols ranging predominantly from C28 to C34 and maximizing at C32 . Minor contributions of benzene-1, 3, 5-triol and derivatives suggested that these aromatic moieties form the polymeric core of cutan, to which the aliphatic moieties are linked via ester and possibly ether bonds. Conclusions: High similarity of aliphatic moieties in the cutan and the cuticular wax component indicated a common biosynthetic origin. In order to exclude species-specific peculiarities of A. americana and to place our results in a broader context, cuticular waxes, cutin and cutan of Clivia miniata, Ficus elastica and Prunus laurocerasus leaves were also investigated. A detailed comparison showed compositional and structural differences, indicated that cutan was only found in leaves of perennial evergreen A. americana and C. miniata, and made clear that the phenomenon of cutan is possibly less present in plant species than suggested in the literature.